The cytotoxic and antiproliferative effect of Polygala saponin XLIV on the human colorectal carcinoma cell line - Becer, Eda; Hanoglu, Azmi; Unlu, Ayse; Aydin, Zuebeyde Ugurlu; Donmez, Ali A.; Jurt, Simon; Calis, Ihsan (Walter De Gruyter Gmbh, 2025)
Objectives Saponins are secondary metabolites naturally found in plants with diverse pharmacological properties such as anticancer. This research aimed to explore the anti-cancer properties of Polygalasaponin XLIV (PS-XLIV) in a human colorectal carcinoma cell line derived from Polygala vulgaris roots.Methods HCT166 cells were treated with different PS-XLIV concentrations and incubated for 24 and 48 h. We used immunocytochemistry to investigate PS-XLIV's anti-cancer properties, employing antibodies targeting WNT3A, WNT11, STAT3, beta-catenin, and Ki-67. The IC50 value of PS-XLIV was 80 mu g/mL in HCT116 cells. WNT11, STAT3, beta-catenin, and Ki-67. Immunoreactivities significantly decreased in PS-XLIV-treated HCT116 cells than in control group cells.Results After PS-XLIV treatment, the epithelial morphology of cells was protected; however, the number of cells was less than that of the control group cells. While WNT3A immunoreactivity was similar in both groups, WNT11 and beta-catenin immunoreactivities were decreased after PS-XLIV application. In addition, the PS-XLIV treated group exhibited significantly weaker Ki-67 immunoreactivity, STAT3 immunoreactivty was moderated after PS-XLIV application.Conclusions For the first time, the anticancer effects of PS-XLIV isolated from P. vulgaris on HCT116 cells were shown. The anticancer effect may involve PS-XLIV reducing WNT11, beta-catenin, STAT3, and Ki-67 activation pathways in HCT116 cells.
Keywords: cancer; colon; Polygala vulgaris; saponin